New perspectives on Neo-Kantianism and the sciences - Pulte, Helmut; Baedke, Jan; Koenig, Daniel; Nickel, Gregor, 1966- (New York, NY : Routledge, Taylor & Francis Group, 2025)
This volume considers the exchange between the Neo-Kantian tradition in German philosophy and the sciences from the last third of the nineteenth century to the Great war and partly beyond.During this period, various scientific disciplines underwent modernisation processes characterised by an increasing empirical inclination and a decline in the influence of metaphysics, the pluralisation of theories, and the historical and pragmatic revitalisation of scientific claims against philosophy. The various contributions look at the ways in which a certain Kantian orthodoxy' was influenced by these new developments and whether (and how) itself had some impact on the development of the sciences. The volume is not limited to the 'exact sciences' of mathematics and physics, which are particularly important for the Kantian tradition, but also takes into account less recognised disciplines such as biology, chemistry, technology and psychology. It is complemented by contributions that contrast Neo-Kantianism with other 'scientific philosophies' of the period in question.
Keywords: Neo-Kantianism.; Science -- Philosophy; PHILOSOPHY / History & Surveys / General; SCIENCE / History; SCIENCE / Philosophy & Social Aspects